Rapid Direct Action of Estradiol in GnRH Neurons: Findings and Implications - Terasawa, Ei (Frontiers in Endocrinology, 2012)
Estradiol plays a pivotal role in the control of GnRH neuronal function and female reproduction. While positive and negative feedback actions of estradiol that enhance and suppress release of GnRH and LH are primarily mediated through estrogen receptor alpha (ERα) located in interneurons, a series of recent studies in our laboratory indicate that rapid excitatory actions of estradiol also directly modify GnRH neuronal activity. We observed this phenomenon in cultured primate GnRH neurons, but similar rapid direct actions of estradiol are also described in cultured GnRH neurons and GFP-labeled GnRH neurons of mice. Importantly, rapid direct action of estradiol in GnRH neurons is mediated through membrane or membrane associated receptors, such as GPR30, STX-sensitive receptors, and ERβ. In this review, possible implications of this rapid estradiol action in GnRH neurons are discussed.